Effects of Chronic Suppression or Oversuppression of Thyroid-Stimulating Hormone on Psychological Symptoms and Sleep Quality in Patients with Differentiated Thyroid Cancer - Altuntaş, Seher Çetinkaya; Hocaoğlu, Çiçek (Hormone and Metabolic Research, 2021)
In differentiated thyroid cancer (DTC), the standard treatment includes total thyroidectomy and lifetime levothyroxine (LT4) replacement. However, long-term exogenous LT4 has become controversial due to the adverse effects of oversuppression. The study included 191 patients (aged 18–76 years) with a prospective diagnosis of non-metastatic DTC and 79 healthy individuals. The patients with DTC were stratified into three groups according to their TSH levels: suppressed thyrotropin if TSH was below 0.1 μIU/ml, mildly suppressed thyrotropin if TSH was between 0.11 and 0.49 μIU/ml, and low-normal thyrotropin if THS was between 0.5 and 2 μIU/ml. The Beck Depression Inventory (BDI), Beck Anxiety Inventory (BAI), Anxiety Sensitivity Index (ASI), Short Symptom Inventory (SSI), and Pittsburgh Sleep Quality Index (PSQI) were administered to all participants. It was found that the BDI, BAI, SSI and PSQI scores were worse in patients with DTC (p=0.024, p=0.014, p=0.012, and p=0.001, respectively). According to theTSH levels, the mean ASI was found to be higher in the suppressed and mildly suppressed thyrotropin groups (19±14.4 vs. 10.6±11.1; 16.4±14.9 vs. 10.6±11.1, p=0.024, respectively), the mean SSI was found higher in the suppressed group (61.0±55.5 vs. 35.1±37.0, p=0.046), and the mean PSQI was higher in all three groups (7.94±3.97 vs. 5.35±4.13; 7.21±4.59 vs. 5.35±4.13; 7.13±4.62 vs. 5.35±4.13, p=0.006) when compared with the controls. No significant difference was found between the groups. A positive correlation was detected in the duration of LT4 use and BDI and SSI, and a weak, negative correlation was detected between TSH levels and ASI and PSQI. Based on our study, it was found that depression, anxiety disorders, and sleep problems were more prevalent in patients with DTC, being more prominent in the suppressed TSH group. These results were inversely correlated with TSH values and positively correlated with the duration of LT4 use. Unnecessary LT4 oversuppression should be avoided in patients with DTC.
Keywords: differentiated thyroid cancer; levothyroxine; subclinical hyperthyroidism; thyroid-stimulating hormone